BIO COMPOSITE MATERIALS AS A SUSTAINABLE SOLUTION FOR MODERN INDUSTRIES - BUICAN, George Razvan; IVASCU, Alexandrina; BENCZE, Andrei (“Henri Coandă” Air Force Academy Publishing House, 2025)
In the global effort to develop circular economy solutions, bio composite materials have emerged as viable, less toxic, and environmentally friendly alternatives to traditional materials. Due to their advantageous physical and mechanical properties, hemp, flax, jute, and bamboo represent renewable resources with significant potential in industries such as aerospace, construction, transportation, and energy. This article investigates the manufacturing processes and tensile strength characteristics of roving’s produced from these materials
The paper explores the potential of bio composite materials as sustainable alternatives to conventional composites in modern industries. Natural fibers such as hemp and jute were combined with bio-epoxy resins to fabricate test specimens. The study investigated manufacturing methods, tensile strength, and failure behavior of these composites, supported by microscopic analysis. The experimental results show that bio composites provide competitive mechanical properties while being renewable, biodegradable, and environmentally friendly. Their applicability is emphasized in aerospace, construction, transportation, and energy sectors, where sustainability and weight reduction are essential. The work confirms that bio composites can contribute to reducing environmental impact and advancing the transition toward a circular economy in materials engineering.
Keywords: Aerospace; bio composite materials; environmental; jute; bio epoxy resin